To explore the effects of different ways of high intensity interval training on self-control and physical health of college students - Sun, Yan; Wang, Yu; Yu, Haohan; Cheng, Kaiwei; Wang, Haoyi; Liu, Jingmin (Frontiers in Public Health, 2025)
ObjectiveThe present study aims to investigate the effects of different modes of high-intensity interval training on the self-control and physical fitness levels of college students.Methods1. The participants of this study comprised 58 college students, who were randomly divided into three groups: an online experimental group (A = 20), an online-offline experimental group (B = 18), and a control group (C = 20). The Chinese Self-Control Scale (CSCS) and the Physical Fitness Level Test (PHLT) were administered to all participants before and after the intervention, and the test results were then assigned to the respective scores. Group A performed online only, Group B performed online-offline Tai Chi practice, 40 min/1 time/week, 30 min/1 time/week jogging and 40 min/2 times/week high-intensity interval training for 8 weeks, and Group C did not undergo high-intensity interval training. 2. Statistical analysis was performed using SPSS 25.0, including one-way ANOVA for pre-test group differences, paired t-tests for within-group differences, and ANOVA and LSD tests for post-test group differences.Results1. A significant improvement in the total score of self-control was observed in group B (p < 0.001), while no significant change was observed in groups A and C. 2. A significant enhancement in standing long jump scores was observed in both groups A and B (p < 0.01 and p < 0.001, respectively), while group A demonstrated a significant enhancement in seated forward bending scores (p < 0.05). Additionally, group B exhibited a substantial improvement in 50-m scores (p < 0.01). The results of the differences between groups showed significant differences in 50-m scores (p < 0.01, B > A; A > C; B > C) and standing long jump scores (p < 0.05, B > A; B > C).Conclusion1. A variety of high-intensity interval training (HIIT) formats have been demonstrated to enhance the physical fitness and health of university students. 2. The online-offline HIIT methodology has been shown to assist in enhancing the self-control of university students. 3. The online-offline HIIT methodology has the capacity to more effectively improve the self-control ability and physical fitness of college students.SuggestionPhysical education teachers implement high-intensity interval training programs using online and offline methods to enhance self-control and fitness in university students.